Correlation between abundance of Windowpane Oyster (Placuna sp) and Characteristics of Sediment on Coastal Waters of Bela River Village Indragiri Hilir Regency Riau Province - Ilcia Teshi Diafana; Afrizal Tanjung; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in January 2015, in the coastal waters of Bela River Village, Indragiri Hilir Regency, Riau Province. The research aimed to determine the correlation between abundance of windowpane oyster (Placuna sp) and characteristics of sediment in the coastal water of Bela River Village. The research used survey method by performing sampling at 3 stations and each station consisted of 4 sampling points. The stations were chosen from 3 different areas namely estuary, settlement area and mangrove environment.The result showed that abundance of windowpane oyster (Placuna sp) in the coastal water of Bela River Village in January was relatively small. The highest abundance on station 3 at the sampling point 2 was 6000 ind/ha. The lowest abundance on station 1 at the sampling point 3 was 1000 ind/ha. Sediment type of Bela River Village Coast was sandy mud. The correlation between abundance of windowpane oyster and sand fraction was negatively correlated with the value of the correlation coefficient r = 0.573. The correlation between abundance of windowpane oyster and mud fraction was positively correlated with the value of the correlation coefficient r = 0.568, and the correlation between abundance of windowpane oyster and organic materials was also positively correlated with the value of the correlation coefficient r = 0.864.Keywords: abundance, sediment, Sungai Bela, windowpane oyster